Pengaruh Keterampilan Mengajar Guru Terhadap Motivasi Siswa pada Pembelajaran Tematik (LPPM UKI Toraja, 2021)
Teacher teaching skills are very important in the learning process in the classroom, because it will determine the success of students. The enthusiasm of the teacher in providing learning for students can be seen from the teaching skills of a teacher. This can affect the effective learning process so that students can be motivated to take part in the learning process in class. Therefore, rakes must fully understand their role in the teaching and learning process in the classroom. With teacher teaching skills, teachers are required to be skilled in carrying out their duties as teachers, with skilled teachers will have a positive impact on their students. This study uses quantitative research with the type of Ex-Posfacto research. The data technique used questionnaires, interviews and documentation. The prerequisite analysis test shows that the data is normally distributed and linear so that the hypothesis testing technique uses simple linear regression analysis. The results showed that the significant value was 0.000. Because 0.000 < 0.05, Ho is rejected and Ha accepted, so it can be stated that there is an effect of teacher teaching skills on student motivation in thematic learning.